Understanding LuxS-based quorum sensing and its inhibition – molecular dynamics simulation study. Issue 7 (3rd May 2018) - Syed, Naima; Ahmed, Ayaz; Moin, Syed Tarique
Abstract: Molecular dynamics simulations were successfully applied to LuxS protein and its protein–ligand complex using the newly developed force field parameters for the iron containing active site. To the best of our knowledge, this was the first attempt to develop force field parameters for the iron containing active site of the LuxS protein. From the simulations, catalytically important amino acid residues were identified which were found to stabilise the ligand. Two residues Glu57 and Asp77 were involved in polar interactions while the protein region in the range between amino acid residue 125 and 131 were predicted to facilitate the entry of ligand to the active site. Other residues like Arg65, Asp77, Ile78 and Ser79 were also recognised as ligand stabilising factors deduced from the simulation. These results were also found to be in good agreement with earlier studies and thus demonstrated the successful application of MD simulations to the LuxS protein. Moreover, the simulation data were expected to be considered for the development of rational approaches in order to identify new LuxS-based quorum sensing antagonists for the treatment of pathologies caused by resistant bacteria.